Why cotton wool spots should not be regarded as retinal nerve fibre layer infarcts. Issue 2 (21st January 2005) - McLeod, D
Abstract : Cotton wool spots (CWSs) comprise localised accumulations of axoplasmic debris within adjacent bundles of unmyelinated ganglion cell axons. Their formation is widely held to reflect focal ischaemia from terminal arteriolar occlusion, but credible evidence supporting this view is lacking. CWSs are here purported to be nothing more than sentinels of retinal nerve fibre layer pathology, hence their recommended redesignation "cotton wool sentinels." After branch arteriolar occlusion, CWSs evolve as boundary sentinels of infarction, their uniform width suggesting a glial constraint to axonal expansion. In pre-proliferative diabetic retinopathy, CWSs form a C-shaped chain nasal to the disc and around the macula where they constitute sentinels of ischaemia affecting the entire retinal mid-periphery. The polymorphous CWSs evolving during acute panretinal hypoperfusion represent sentinels of an ischaemic penumbra. Those surrounding the disc in Purtscher's traumatic angiopathy are sentinels of neuronal damage from transient venous hyperdistension that overwhelms the protection afforded by peripapillary axonal decompartmentalisation.